Durability of steel rail bridges as a part of environmental protection - Savchuk, Petro; Maksymovych, Olesya; Knysh, Vitaliy (Budownictwo i Architektura / Civil and Architectural Engineering, 2016)
Condition of bridges with defects can lead to destruction and at the same time adverse effects on the environment, causing discomfort to society. Therefore, it is necessary to predict the durability of existing bridges, including resistance to increasing number of fatigue cracks, which can lead to the destruction of the steel elements. The article presents the results of theoretical and experimental research, which can be used to assess the durability of steel structures. The method of calculation of fatigue cracks growth in anisotropic elements, occurring at different angles to the stiffeners, was presented in the paper. Developed calculation allows estimating time of growth of cracks to some (safe) sizes and determining a value of stress intensity factors, based on which major repairs of the damaged areas can be planned.